2016
DOI: 10.1016/j.jchf.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter-Defibrillator Use in Patients With Left Ventricular Assist Devices

Abstract: ICD use was associated with a significant reduction in mortality in LVAD patients, however, this effect was not significant in patients with CF-LVADs. Although these data support the use of ICDs, larger randomized trial data are strongly warranted to evaluate ICD effectiveness in patients with current generation LVADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 27 publications
4
49
1
6
Order By: Relevance
“…Incidence of VA (defined as sustained ventricular tachyarrhythmias lasting >30 s or requiring ICD therapy) and ICD shocks following CF‐LVAD implantation in our study was comparable to the previous studies evaluating this 6, 21, 22, 27, 29. However, in contrast to the prior study from Schleifer et al,14 we did not observe any significant reduction in the incidence of VA or ICD shocks in the CRT group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Incidence of VA (defined as sustained ventricular tachyarrhythmias lasting >30 s or requiring ICD therapy) and ICD shocks following CF‐LVAD implantation in our study was comparable to the previous studies evaluating this 6, 21, 22, 27, 29. However, in contrast to the prior study from Schleifer et al,14 we did not observe any significant reduction in the incidence of VA or ICD shocks in the CRT group.…”
Section: Discussionsupporting
confidence: 80%
“…Data regarding the impact of ICD therapy on survival in LVAD recipients, however, have been conflicting. Two recent meta‐analyses of available observational studies show no significant survival benefit for ICD therapy in CF‐LVAD recipients 27, 28. Our data also did not show any significant independent association between the type of cardiac implantable electronic device (ICD versus CRT) and survival.…”
Section: Discussioncontrasting
confidence: 52%
“…This analysis found a relative risk of 0.61 for all-cause mortality with a confidence interval of 0.46 to 0.82 (p o 0.01). 15 The major concern with these data is their generalizability to modern LVAD therapy, where the vast majority of patients are implanted with CF devices and have pre-existing ICDs in situ. As such, there is concern that the survival trend observed in this meta-analysis is likely to be confounded by a higher overall intensity of care, or by a selection bias toward patients with a better prognosis in individuals with an ICD implanted.…”
Section: Icd Therapy In Lvad Patientsmentioning
confidence: 99%
“…Two recent meta-analyses combining data from these prior small studies on ICD efficacy concluded that there is no survival benefit with ICD in LVAD patients and urged the need for a randomized clinical trial [9,10].…”
Section: Clinial Studies Assessing the Effects Of Icd In Continuous Fmentioning
confidence: 99%
“…In LVAD recipients, however, there remains an increased risk for ventricular tachyarrhythmias (VTAs) that has been shown to adversely impact outcomes [6,7]. Recommendations from the International Society of Hert and Lung Transplantation therefore suggest reactivation of an ICD following an LVAD placement (Class I, Level of Evidence A), and implantation of an ICD in those with no ICD before LVAD (Class IIa, Level of Evidence B) [8], based on small retrospective studies, expert consensus, or meta-analyses [9,10]. Despite such recommendations, whether an ICD is associated with survival benefit in LVAD patients remains controversial.…”
Section: Introductionmentioning
confidence: 99%